EKSISTENSI SANAD DALAM HADIS - Zulheldi Zulheldi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: The Existence of Chain of Transmitters of Prophetic Tradition. The chain of transmitters (sanad) plays an important role not only in determining the qualification of prophetic tradition but also in Islamic studies in general. In addition, scholars of hadîth have regarded chain of transmitters as citadel and mace of Muslim society. The author argues that the existence of sanad distinguishes Islamic community from other religious groups in reconstructing the authenticity of the teaching of the Islam. It is for this reason that scholars of hadîth have invested a great deal of efforts and serious study on sanad until they were finally capable of formulating a general theory that shall become guidelines in the study of prophetic tradition. This paper is an attempt to discuss the historical origin of sanad criticism as well as analyze the extent to which this theory contributes to verifying the authenticity of Islamic precepts.Kata Kunci: sanad, matn, shahîh, hadis maudhu‘